Can preoperative percutaneous injection of ultrasound contrast agent locate sentinel lymph nodes of breast cancer? - Huang, Dayan; Cao, Wenbin; Luo, Yunhao; Guan, Cheng; Liu, Yuyan; Li, Chaonan; Chen, Jie; Luo, Jing; Luo, Jun (Frontiers in Oncology, 2024)
ObjectivesWe evaluated the ability and accuracy of preoperative identification and localization of sentinel lymph nodes (SLNs) using intradermal injection of ultrasound contrast agent.Materials and methodsProspectively recruited 191 early breast cancer patients with clinically negative axillary lymph nodes (ALNs). All participants received intradermal injection of microbubble contrast agent. Following the identification and localization of SLNs using contrast-enhanced ultrasound (CEUS), Markers were deployed in the SLNs US-guided. Subsequently, the SLNs with Markers were stained and marked with a suspension of nano-carbon US-guided to assist in intraoperative localization of SLNs. Standard SLNB with methylene blue tracing was performed intraoperatively to assess the consistency between the two methods of SLNs localization, thereby determining the ability and accuracy of CEUS in identifying and localizing SLNs.ResultsA total of 179 patients were included in the final evaluation analysis, in which a microbubble contrast agent was injected subcutaneously in the areolar region. A total of 201 SLNs were identified, with a median of 1 SLN per patient. Each SLN was identified in 157 patients, and two SLNs were identified in 22 patients. Among the 201 SLNs from the 179 patients, the proportion that could be individually matched between CEUS and the blue dye method was 95.5% (192/201), and the consistency evaluation in SLNs identification between CEUS and blue dye staining was excellent (Kappa value = 0.62, P < 0.001).ConclusionThe consistency of identification and localization of SLNs in early breast cancer patients between CEUS and the blue dye method was strong.